2020
DOI: 10.3390/ijerph17165710
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Lockdown, Food Systems and Urban–Rural Partnership: Case of Nagpur, India

Abstract: The globally fast-spreading novel coronavirus disease (COVID-19) is now testing the abilities of all countries to manage its widespread implications on public health. To effectively contain its impacts, a nation-wide temporary lockdown was enforced in India. The resultant panic buying and stockpiling incidents together with spread of misinformation created a sense of food insecurity at local level. This paper discusses a specific case of Nagpur from the worst affected Maharashtra state of India, wherein the ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 41 publications
2
53
0
1
Order By: Relevance
“…The results show that stay-at-home orders (SAHO) and partial lockdowns that SSA governments implemented as measures to prevent the spread of the virus were associated with amplified food security worries (Arndt et al 2020 ). Several recent studies have found that mobility restrictions and social distancing measures due to COVID-19 have further triggered consumers’ worries about food insecurity, reflected in hoarding behaviours, panic-buying and stockpiling of groceries and rapid changes in food consumption habits and diets (Coopi 2020 ; FEWSNET 2020 ; Sukhwani et al 2020 ; Pulighe and Lupia 2020 ). It is not surprising that individuals hoarded food given the demonstrated association between food, nutrition and health, especially in boosting the immune systems and reducing susceptibility to infection (Naja and Hamadeh 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results show that stay-at-home orders (SAHO) and partial lockdowns that SSA governments implemented as measures to prevent the spread of the virus were associated with amplified food security worries (Arndt et al 2020 ). Several recent studies have found that mobility restrictions and social distancing measures due to COVID-19 have further triggered consumers’ worries about food insecurity, reflected in hoarding behaviours, panic-buying and stockpiling of groceries and rapid changes in food consumption habits and diets (Coopi 2020 ; FEWSNET 2020 ; Sukhwani et al 2020 ; Pulighe and Lupia 2020 ). It is not surprising that individuals hoarded food given the demonstrated association between food, nutrition and health, especially in boosting the immune systems and reducing susceptibility to infection (Naja and Hamadeh 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…With regard to urban areas, COVID-19 has expanded in many cities to a crisis of urban equity, urban finance, safety, joblessness or labour layoffs, public services, infrastructure and transport, all of which are disproportionately affecting the most vulnerable in society (UN 2020b ). In rural areas of developing countries, the ability to produce and consume one’s own food may be somewhat protective of food and diets during extreme events (Sukhwani et al 2020 ). However, poverty and informal employment rates are generally higher in rural areas, whereas access to social networks is relatively lower, which combines to create a situation of extreme vulnerability (FAO-CELAC 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have also raised concerns that COVID-19 may threaten the implementation of the sustainable development goals (Fleetwood 2020 ; Leal Filho et al 2020 ; Sakamoto et al 2020 ). To address the problems of food supply, researchers have been proposing different strategies like urban agriculture (Pulighe and Lupia 2020 ), urban-rural collaborations (Cattivelli and Rusciano 2020 ; Sukhwani et al 2020 ), shorter supply chains (Pulighe and Lupia 2020 ), and use of innovative agri-food systems based on artificial intelligence (Di Vaio et al 2020 ). These studies highlight the need of alternative food systems having high resilience to such global crisis.…”
Section: Resultsmentioning
confidence: 99%
“…), and their interactions along the various stages of the food value chain, such as production, storage, processing, transportation, distribution, etc. [11]. The COVID-19 pandemic has particularly affected these interactions.…”
Section: Introductionmentioning
confidence: 99%